Kreowanie wizerunku biblioteki akademickiej na podstawie działań public relations Biblioteki Politechniki Wrocławskiej - Wojtczak, Jadwiga (Biblioteka Uniwersytecka w Poznaniu, 2013)
Dążenie do budowy pozytywnego wizerunku dotyczy nie tylko przedsiębiorstw czy firm komercyjnych. Budowanie relacji z otoczeniem nabiera coraz większego znaczenia w instytucjach non profit, do których zaliczane są między innymi biblioteki. Celem artykułu jest przedstawienie działań promocyjnych realizowanych w bibliotece akademickiej. Na wstępie omówiono podstawowe pojęcia związane z public relations i wizerunkiem. Posłużono się przykładem Biblioteki Politechniki Wrocławskiej, która od wielu lat z pozytywnym skutkiem stosuje różnorodne techniki public relations. Bibliotekę czekają nowe wyzwania w związku ze zbliżającym się w 2013 roku terminem zakończenia budowy Środowiskowej Biblioteki Nauk Ścisłych i Technicznych na potrzeby Innowacyjnej Gospodarki – pierwszej w Polsce biblioteki oferującej zasoby wyłącznie w formie elektronicznej.

The ambition to create a favourable image of an organization is not exclusively important for corporate or commercial companies. Building a fair and constructive relations with the environment has also become more and more crucial for non-profit organizations such as, for example, libraries. This article aims to present promotional services that are usually performed at a typical academic library. The first part of the article includes an introduction to the basic terms and notions related to public relations and image-creating activities. The library of Wrocław university of technology is the case example in a presentation of the endeavours aiming at an improvement of these relationships. The library has been successfully implementing a number of different public relations techniques for many years. Currently, the library faces new challenges following the completion, in 1913, of the new environmental science and engineering library, the first library in Poland that would offer its resources exclusively in electronic form.
Creating an image of an academic and research library on the basis of the public relations approach. A case study for the library of Wrocław University of Technology
Keywords: marka; promocja; tożsamość; biblioteka akademicka; komunikacja społeczna; brand; promotional activities; academic library; social communication